The effectiveness of financial management in the system of ensuring the security of trading enterprises in the domestic market in wartime conditions - Polehenka, Maryna; Полегенька, Марина Анатоліївна; Sitkovska, Alla; Сітковська, Алла Олександрівна; Viblyi, Petro; Віблий, Петро; Danchak, Lesia; Данчак, Леся; Khavarivska, Halyna; Хаварівська, Галина (Fintechalliance LLC, 2025)
The purpose of the study was to substantiate the effectiveness of financial management in the system of ensuring the security of trading enterprises and to assess the effectiveness of such decisions in wartime. The paper examines the role of financial management in ensuring the security of enterprises in the domestic market of Ukraine during the war. To achieve this goal, a database of financial indicators of three Ukrainian trading companies for 2020–2023 was formed. The integral indicator of financial management effectiveness (IFE) was calculated by normalizing key financial ratios. To identify the causal impact of the war and the growth of the "security budget" on IFE, a panel regression model with fixed effects and the "difference-in-differences" methodology was used. It was found that, provided that a sufficient level of liquidity was maintained and the debt burden was controlled, individual enterprises were able to maintain (or even improve) their financial efficiency, despite the increase in security costs. This emphasizes the importance of balanced financial management for business sustainability in wartime. Based on the results of the analysis, practical recommendations were developed regarding the minimum liquidity reserve and the optimal level of security costs, compliance with which will help minimize the negative impact of risk factors on the financial performance of enterprises. Метою проведеного дослідження було обґрунтувати ефективність фінансового менеджменту в системі забезпечення безпеки торговельних підприємств та оцінити ефективність таких рішень у воєнний час. У роботі розглянута роль фінансового менеджменту в забезпеченні безпеки підприємств внутрішнього ринку України під час війни. Для реалізації мети було сформовано базу фінансових показників трьох українських торговельних компаній за 2020– 2023 роки. Розраховано інтегральний показник ефективності фінансового управління (IFE) шляхом нормалізації ключових фінансових коефіцієнтів. Для виявлення причиново-наслідкового впливу війни та зростання «бюджету безпеки» на IFE застосовано панельну регресійну модель із фіксованими ефектами й методологію «різниця-в-різницях». Виявлено, що за умови підтримання достатнього рівня ліквідності та контролю боргового навантаження окремі підприємства спромоглися зберегти (або навіть поліпшити) свою фінансову ефективність, незважаючи на зростання витрат на безпеку. Це підкреслює важливість збалансованого фінансового менеджменту для стійкості бізнесу в умовах воєнного часу. За підсумками аналізу розроблено практичні рекомендації щодо мінімального резерву ліквідності та оптимального рівня витрат на безпеку, дотримання яких допоможе мінімізувати негативний вплив факторів ризику на фінансову результативність підприємств.
Ефективність фінансового менеджменту в системі забезпечення безпеки торговельних підприємств на внутрішньому ринку в умовах воєнного часу
Keywords: financial management; фінансовий менеджмент; security development; безпековий розвиток; trading enterprises; торговельні підприємства; management; управління; efficiency assessment; оцінювання ефективності; domestic market; внутрішній ринок; martial law; воєнний стан